2023
DOI: 10.3390/ijerph20075260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Provider and Leader Perspectives about Concurrent Tobacco-Use Care during Substance-Use Treatment on Their Tobacco Intervention Provision with Clients: A Mixed-Methods Study

Abstract: People with substance-use disorders have elevated rates of tobacco use compared with the general population, yet rarely receive tobacco-dependence treatment within substance-use treatment settings (SUTS). One barrier to delivering evidence-based interventions in SUTS is providers’ misconception that treating tobacco use and non-nicotine substance use concurrently jeopardizes clients’ substance-use recovery, although research indicates that it enhances support for recovery and relapse prevention. A total of 86 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…However, we also encountered attitudes indicating that staff, including clinicians, were doubtful about their clients’ interest in quitting and ability to do so. Given their expertise and supportive roles as addiction treatment specialists, clinicians’ attitudes can greatly affect those of their clients; moreover, clinicians’ beliefs and attitudes are often cited as one of the major barriers to effectively implementing tobacco-free programs within substance use treatment settings [ 4 , 22 , 25 , 57 ]. Training given as a part of the program implementation provided staff with information on evidence-based tobacco cessation practices and addressed some of these attitudes to better prepare staff to provide cessation care to their clients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also encountered attitudes indicating that staff, including clinicians, were doubtful about their clients’ interest in quitting and ability to do so. Given their expertise and supportive roles as addiction treatment specialists, clinicians’ attitudes can greatly affect those of their clients; moreover, clinicians’ beliefs and attitudes are often cited as one of the major barriers to effectively implementing tobacco-free programs within substance use treatment settings [ 4 , 22 , 25 , 57 ]. Training given as a part of the program implementation provided staff with information on evidence-based tobacco cessation practices and addressed some of these attitudes to better prepare staff to provide cessation care to their clients.…”
Section: Discussionmentioning
confidence: 99%
“…Our use of “staff” here refers to both clinical employees, those providing direct services to clients, and nonclinical employees. Moreover, despite evidence to the contrary, staff may believe that treating tobacco use and substance use disorders simultaneously will jeopardize substance use treatment and recovery [ 25 ]. Together, these barriers and others may contribute to the known translational lag whereby any type of evidence-based practice takes a long time (e.g., up to 17 years) to be implemented into practice to reach the intended population and ensure the improvement of clients’ health [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The University of Houston Institutional Review Board (IRB) concluded that this project did not meet the definition of human subjects research under 45 CFR 46.102 (I) (i.e., a systematic investigation, including research development, testing, and evaluation, designed to develop or contribute to generalizable knowledge); therefore, no IRB review/approval was necessary. Detailed recruitment procedures are described elsewhere ( Siddiqi et al, 2022 , Taing et al, 2022 , Jafry et al, 2022 , Britton et al, 2023 , Britton et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%